Chemical contaminants in juvenile gray whales ( Eschrichtius robustus ) from a subsistence harvest in Arctic feeding grounds - Tilbury, Karen L.; Stein, John E.; Krone, Cheryl A.; Brownell, Robert L., Jr.; Blokhin, S.A.; Bolton, Jennie L.; Ernest, Don W. (DigitalCommons@University of Nebraska - Lincoln, 2002)
Gray whales are coastal migratory baleen whales that are benthic feeders. Most of their feeding takes place in the northern Pacific Ocean with opportunistic feeding taking place during their migrations and residence on the breeding grounds. The concentrations of organochlorines and trace elements were determined in tissues and stomach contents of juvenile gray whales that were taken on their Arctic feeding grounds in the western Bering Sea during a Russian subsistence harvest. These concentrations were compared to previously published data for contaminants in gray whales that stranded along the west coast of the US during their northbound migration. Feeding in coastal waters during their migrations may present a risk of exposure to toxic chemicals in some regions. The mean concentration (standard error of the mean, SEM) of Σ PCBs [1400 (130) ng/g, lipid weight] in the blubber of juvenile subsistence whales was significantly lower than the mean level [27 000 (11 000) ng/g, lipid weight] reported previously in juvenile gray whales that stranded in waters off the west coast of the US. Aluminum in stomach contents of the subsistence whales was high compared to other marine mammal species, which is consistent with the ingestion of sediment during feeding. Furthermore, the concentrations of potentially toxic chemicals in tissues were relatively low when compared to the concentrations in tissues of other marine mammals feeding at higher trophic levels. These chemical contaminant data for the subsistence gray whales substantially increase the information available for presumably healthy animals.